THE INFLUENCE OF EDUCATION AND WORK EXPERIENCE ON WORK ETHIC WITH PROFESSIONALISM AS A MODERATING VARIABLE IN EMPLOYEES OF THE MEDAN CITY GOVERNMENT SMALL AND MEDIUM BUSINESS COOPERATIONS OFFICE - Orlanda, Bella; Nahrisah, Ezzah; Hafas, Hafriz Rifki (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research aims to find out whether education and work experience influence work ethic with professionalism as a moderating variable in the Medan City Government's Department of Cooperatives, Small and Medium Enterprises, Industry and Trade. The analysis technique used is multiple linear regression analysis MRA- Moderated Regression Analysis. This research uses associative research with a quantitative approach. Data collection techniques were obtained from questionnaires. The population and the sample in this study was 99 people using a saturated sampling method, namely a sample that also represents the total population. The research results show that the variables of education and work experience have a significant influence on work ethic. For the Professionalism variable which acts as a moderating variable, in this research the professionalism variable is able to significantly moderate the education and work experience variables on work ethic.)